Algorithm of diagnostics of erectile dysfunction in patients with arterial hypertension and dynamics of arterial blood pressure against the background of androgenic deficiency - Vintoniv, O.R.; Popadynets, I.R.; Hrodzinskyy , V.I.; Melnyk , S.V.; Herych, P.R.; Halipchak , I.M. (Medicni Perspektivi, 2021)
In recent years, the requirements for the level of the life quality have increased significantly; an integral part of it is the sexual harmony, which in men largely depends on sexual desire and erectile function. According to the results of modern scientific studies, there is no doubt that erectile dysfunction in men is closely connected with the cardiovascular diseases, obesity, diabetes mellitus and other comorbidities. This problem can also be caused by systematic psycho-emotional overload, deterioration of the environmental conditions, harmful factors of production, uncontrolled use of medicines, inflammatory processes in the genital organs, the growth of somatic diseases. The vast majority of works concerning “male menopause” is reduced to the effectiveness of hormone-replacement therapy in erectile dysfunction, while only few research works are devoted to the study of the connection between somatic pathology and androgen deficiency. There is a negative correlation between total testosterone level and systolic blood pressure. According to the research results of some scientists, it was found that 38% of patients with arterial hypertension had androgen deficiency, confirmed in the laboratory, which is significantly higher than in patients of the same age category with normal blood pressure. These dominant factors exert and increase the influence on each other, which must be taken into account in modern therapeutic practice. The study of the formation of comorbid conditions in men with low levels of androgens is of particular importance, as the knowledge of pathophysiological mechanisms can prevent their development and progression. The aim of this investigation was to study the state of penile vascular blood flow in men with arterial hypertension with erectile dysfunction, using color Doppler imaging with pharmacological induction of erection. The indicators of daily monitoring of arterial pressure and arterial stiffness in men with arterial hypertension of the II degree against the background of androgen deficiency or at normal testosterone levels and ways of correction of erectile dysfunction in these patients were also evaluated.